2019
DOI: 10.20944/preprints201908.0320.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistence Landscape based Topological Data Analysis for Personalized Arrhythmia Classification

Abstract: Data can be illustrated in shapes, and the shapes could provide insight for data modeling and information extraction. Topological data analysis provides an alternative insight in biomedical data analysis and knowledge discovery with the algebra topology tools. In present work, we study the application of topological data analysis for personalized electrocardiographic signal classification toward arrhythmia analysis. Using phase space reconstruction technique, the signal samples are converted into point clouds … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In another recent study, Yan and coworkers [16] explored the use of topological data analysis to classify electrocardiographic signals and detect arrhythmias. Cardiac arrhythmias are abnormal heart rhythms or irregularities in the heartbeat that may be too fast (tachycardia), too slow (bradycardia), or irregular.…”
Section: Ecg Data and Heart Rate Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another recent study, Yan and coworkers [16] explored the use of topological data analysis to classify electrocardiographic signals and detect arrhythmias. Cardiac arrhythmias are abnormal heart rhythms or irregularities in the heartbeat that may be too fast (tachycardia), too slow (bradycardia), or irregular.…”
Section: Ecg Data and Heart Rate Signalsmentioning
confidence: 99%
“…In the particular case of reference [16], phase space reconstruction was used to convert the signals into point clouds, which were then analyzed using topological techniques to extract persistence landscapes as features for the classification task. The authors found that the proposed method was effective, with a normal heartbeat class recognition rate of 100% when using just 20% of the training set, and recognition rates of 97.13% for ventricular beats, 94.27% for supraventricular beats, and 94.27% for fusion beats.…”
Section: Ecg Data and Heart Rate Signalsmentioning
confidence: 99%
“…Study ( Graff et al, 2021 ) examined when persistence diagram was obtained by SLS filtering, and a set of indicators was extracted to distinguish the RR interval of healthy subjects and stroke patients. In addition ( Yan et al, 2019 ) applied TDA to reconstruct a signal point cloud to extract persistent landscape features to classify heart rate variability. The accuracy of a normal heartbeat was 100%, of ventricular beating was 97.13%, of supraventricular beating was 94.27%, and of fusion beating was 94.27%.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, some studies have proposed the use of TDA metrics as a preliminary stage to extract features for machine learning classifiers, e.g., for medical image analysis [16,17,18], chemical components [19,20], or computer science problems [21]. Thus, these classification problems do not operate in the multidimensional dataset or in a subsequent reduced dimensionality space [22,23], but rather in the domain of meaningful topological feature vectors [24,25,26], with a consequent interpretability gain.…”
Section: Introductionmentioning
confidence: 99%